Exploring the Multidimensional Landscape of Sustainable Finance: A Thematic Analysis Approach - Gohar Ayaz; Zahid, Muhammad (Journal of Business & Tourism, 2023)
This study aims to comprehensively explore the multidimensional landscape of sustainable finance through a thematic analysis approach. With a dataset of 138 articles retrieved from the Scopus database, the study employs VOSviewer for co-word analysis, revealing four interconnected thematic clusters. These clusters, representing economic, environmental, social, and governance dimensions, provide a structured framework that underscores the intricate relationships within sustainable finance. The findings illuminate the interplay between these dimensions, offering valuable insights for researchers, practitioners, and policymakers to navigate the complex field of sustainable finance and promote informed decision-making. The implications of this study extend to fostering more holistic financial practices that consider economic growth, environmental preservation, social equity, and ethical governance in tandem, thereby contributing to a more responsible and inclusive financial future.